Tahlilu al-Jawanib al-Balaghiyah fi Kitab Durus fi al-Nushush al-Adabiyah al-Mustawa al-Rabi' bi Ma'had Ta'lim al-Lughah al-'Arabiyah li Ghairi al-Nathiqina biha fi al-Jami'ah al-Islamiyah bi al-Madinah al-Munawwarah - Hamdy, Mohammad Zainal; Mubarak, Sabiqul (Dzil Majaz: Journal of Arabic Literature, 2024)
This research aims to analyze the rhetorical aspects in the book Lessons in Literary Texts, Level Four, a book that is scheduled at the Institute for Teaching Arabic Language to Non-Native Speakers at the Islamic University of Medina. One of the objectives of this research is to uncover the rhetorical aspects in this book and its types in particular and other books in general. In this research, the researcher uses a qualitative study method that collects data from words and opinions and a method of analyzing the data. The researcher uses the method of analyzing the subject in the book, by having the researcher read the book, then the researcher extracts Words that have rhetorical aspects. The researcher reads books on the sciences of rhetoric to learn about the sciences of rhetoric and what is related to it. After that, the researcher explains the rhetorical aspects in that researched book, analyzing and discussing them in detail and explanation. The results of the research indicate that in the book “Lessons in Literary Texts, Level Four, at the Institute for Teaching Arabic to Non-Native Speakers at the Islamic University of Medina,” there are 71 diverse rhetorical aspects. As they are: 9 counterpoint, 5 opposite, 4 restricting what is described to the adjective, 6 restricting the adjective to what is described, 10 simile, 3 declarative metaphor, 5 spatial metaphor, 8 metonymy, 5 transmitted metaphor, 3 mental metaphor, 3 mentioning the specific after the general, 2 Mention of the specific after the general, 3 Exaggeration, 5 Denial interrogative. This research indicates that the science of rhetoric is very important for knowing literature and beauty in the Arabic language and knowing what is meant in ancient or modern literary texts